Transitional justice in public and private: truth commission narratives in Greensboro - Fox, Nicole (International journal of transitional justice, 2022)
In 1979, during an anti-racism march in the city in Greensboro, North Carolina, KKK and Nazi Party members opened fire on demonstrators, killing five and wounding eight. On the cusp of the 25th anniversary of these killings, efforts by community members culminated in the convening of the first Truth and Reconciliation Commission (GTRC) in the US. Drawing on a unique collection of public testimonies and private interviews with GTRC staff, we use a novel relational approach to array and compare discursive accounts offered in these distinct settings. We find that narratives offered in private were more varied, yet also cohesive in locating blame in social actors. Public testimony, in contrast, was more consolidated and singular, placing the majority of culpability on social structures. Based on these significant distinctions, we draw out implications for future research and policy around transitional justice initiatives.